School Leadership and Curriculum: German Perspectives. Issue 2 (3rd April 2017) - Huber, Stephan; Tulowitzki, Pierre; Hameyer, Uwe
ABSTRACT: This article looks at the role of school leadership vis-à-vis the curriculum. First, it offers a brief overview of school leadership in Germany. Next, curriculum development and curriculum research in Germany is briefly recapped. We present empirical data on school leadership preferences, strain experience, and practices as to curriculum work. Then the discussion is linked to the international discourse on instructional leadership. Next, we conclude with the concept of organizational education (Organisationspädagogik) as a perspective for viewing school leadership in conjunction with the curriculum. Finally, based on the material presented before, we take a reflective look ahead and ponder possibilities and desiderata of school leadership in the context of curriculum.